Search
Ask a question
0

How do you solve y^2(y^-2)

When multiplying y ^2 by y^-2 do you add the exponents?  If so that would be zero correct?
 

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Philip P. | Effective and Affordable Math TutorEffective and Affordable Math Tutor
4.9 4.9 (382 lesson ratings) (382)
2
Yes, you are right, Nicholas; the rule for multiplying two exponential terms with the same base is:
 
yayb = ya+b
 
So, yes, you are right again:
 
y2y-2 = y2+(-2) = y0
 
Now what does y0 = ?  (Hint: it's not zero)

Comments

y^0 =1 only if y≠0.